2002
DOI: 10.1890/0012-9615(2002)072[0133:eosupa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF SEA URCHINS (PARECHINUS ANGULOSUS) ON RECRUITS AND JUVENILES OF ABALONE (HALIOTIS MIDAE)

Abstract: Much current research on community ecology concerns indirect effects, cascading trophic interactions, and the role of top‐down vs. bottom‐up processes, as well as subsidization of matter and energy between different systems. We addressed all these topics by exploring interactions between the urchin Parechinus angulosus and both recruits and juveniles of the abalone Haliotis midae, in the light of the fact that juvenile abalone shelter beneath the urchins. In field experiments at six sites, urchins were elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 71 publications
(21 reference statements)
1
44
3
Order By: Relevance
“…In particular, changes in community structure at Stairs were largely driven by an increase in the number of urchins, which may compete with abalone for resources (Davis et al 1992, Day & Fleming 1992, but may also maintain appropriate habitat for abalone recruitment through grazing of foliose algae and increasing the cover of crustose coralline algae (McShane 1992). Additionally, abalone recruits might benefit from the presence of sea urchins as a source of shelter from predation, as well as an enhanced food supply (Rogers-Bennett & Pearse 1998, Day & Branch 2002b, Day & Branch 2002c, Tomascik & Holmes 2003, although this relationship has not been demonstrated for Haliotis cracherodii and the relatively short-spined Strongylocentrotus pupuratus, which predominates in this intertidal region. Therefore, in the narrow crevices at Stairs it might be argued that habitat suitable for abalone recruitment persisted following the mass mortalities, yet there was still no abalone recruitment, supporting the contention that inadequate larval supply is limiting black abalone recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, changes in community structure at Stairs were largely driven by an increase in the number of urchins, which may compete with abalone for resources (Davis et al 1992, Day & Fleming 1992, but may also maintain appropriate habitat for abalone recruitment through grazing of foliose algae and increasing the cover of crustose coralline algae (McShane 1992). Additionally, abalone recruits might benefit from the presence of sea urchins as a source of shelter from predation, as well as an enhanced food supply (Rogers-Bennett & Pearse 1998, Day & Branch 2002b, Day & Branch 2002c, Tomascik & Holmes 2003, although this relationship has not been demonstrated for Haliotis cracherodii and the relatively short-spined Strongylocentrotus pupuratus, which predominates in this intertidal region. Therefore, in the narrow crevices at Stairs it might be argued that habitat suitable for abalone recruitment persisted following the mass mortalities, yet there was still no abalone recruitment, supporting the contention that inadequate larval supply is limiting black abalone recovery.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study at a nearby location also found low rates of grazing, although densities of sea urchins were markedly higher (5.8 m -2 ; Vanderklift & Wernberg 2008). There is increasing evidence that, although grazing by sea urchins undoubtedly modifies ecosystems at some places, density of sea urchins alone does not lead to high rates of grazing, as many species assume a drift-feeding behaviour (Castilla & Moreno 1982, Harrold & Reed 1985, Day & Branch 2002a, Shears et al 2008.…”
Section: Low Rates Of Grazing By Fish and Sea Urchinsmentioning
confidence: 99%
“…Because of its size, meat quality and market value, it is considered as one of the most soughtafter and valuable marine molluscs of the African continent. Consequently, it suffers from overexploitation and together with ecological factors such as changes in habitat quality and predation pressure, has declined significantly over the last few decades (Hauck and Sweijd 1999;Day and Branch 2002). The species has also been listed in CITES Appendix III in 2007 but has since been removed.…”
Section: Introductionmentioning
confidence: 99%